Analisis dan Eksplorasi Kebutuhan Pengembangan Media Pembelajaran Digital Apresiasi Puisi di Sekolah Dasar - Qikha Maulidhia; Seni Apriliya; Asep Nuryadin (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is motivated by advances in educational technology to improve the quality of students' learning and the importance of using digital media to make the process of literary learning activities easier to understand. One of the literary lessons that is introduced to students is poetry appreciation. The poetry appreciation learning process requires digital learning media to help students understand, appreciate and assess the content of poetry in the poetry appreciation learning process. This research aims to analyze and explore the need for developing digital learning media for poetry appreciation in class IV elementary schools. This research uses a method, namely a qualitative descriptive method. The data collection techniques used were observation sheets, interview guides and content analysis. Based on the results of the analysis and exploration of the learning media needs of the two educators, it shows that there are educators who still do not use digital learning media or media that is specific or focused on learning poetry appreciation. It is hoped that further research can reveal learning results from analysis and exploration of the need to develop digital learning media in accordance with the stages of poetry appreciation, including students being able to understand, appreciate and assess the content of the poetry presented.